2000
DOI: 10.1128/aem.66.9.4157-4160.2000
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Triclosan by Trametes versicolor and Pycnoporus cinnabarinus

Abstract: We investigated the ability of Trametes versicolor and Pycnoporous cinnabarinus to metabolize triclosan. T. versicolor produced three metabolites, 2-O-(2,4,4-trichlorodiphenyl ether)-␤-D-xylopyranoside, 2-O-(2,4,4-trichlorodiphenyl ether)-␤-D-glucopyranoside, and 2,4-dichlorophenol. P. cinnabarinus converted triclosan to 2,4,4-trichloro-2-methoxydiphenyl ether and the glucoside conjugate known from T. versicolor. The conjugates showed a distinctly lower cytotoxic and microbicidal activity than triclosan did.Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 27 publications
4
46
1
Order By: Relevance
“…No decrease in triclosan was seen in uninoculated samples or those inoculated with E. coli (data not shown). Conjugated products of triclosan, as previously identi¢ed in triclosan detoxi¢cation by T. versicolor and P. cinnabarinus [11], were not observed in P. putida TR1 or A. xylosoxidans TR1 culture extracts at 280 nm, since there was a single peak with the identical retention time of triclosan. Combined with the growth of P. putida TriRY and A. xylosoxidans TR1 in medium containing triclosan as a sole carbon source and the ability of these isolates to detoxify triclosan-containing media and plastics, degradation appears to be the mechanism of triclosan detoxi¢cation by these bacteria.…”
Section: Resultsmentioning
confidence: 66%
“…No decrease in triclosan was seen in uninoculated samples or those inoculated with E. coli (data not shown). Conjugated products of triclosan, as previously identi¢ed in triclosan detoxi¢cation by T. versicolor and P. cinnabarinus [11], were not observed in P. putida TR1 or A. xylosoxidans TR1 culture extracts at 280 nm, since there was a single peak with the identical retention time of triclosan. Combined with the growth of P. putida TriRY and A. xylosoxidans TR1 in medium containing triclosan as a sole carbon source and the ability of these isolates to detoxify triclosan-containing media and plastics, degradation appears to be the mechanism of triclosan detoxi¢cation by these bacteria.…”
Section: Resultsmentioning
confidence: 66%
“…strain RD1, where loss of the ability to mineralize triclosan resulted in susceptibility to this biocide (28). While the authors are not aware of any bacteria that can modify triclosan, O-glucosyation and O-xylosylation of this biocide have been demonstrated in at least two fungi (25), and we should not be too surprised to find similar modification mechanisms in bacteria. Biofilm-grown Salmonella enterica serovar Typhimurium was triclosan tolerant, and it was suggested that Salmonella bacteria within biofilms could experience reduced influx (64).…”
mentioning
confidence: 93%
“…There are no data available for the influence of 250 g of this mixture ml Ϫ1 on the growth of the yeast cells because of the limited amount of this mixture enriched by semipreparative HPLC. (18). In contrast, conjugates with hydroxylated intermediates were not found during biphenyl transformation by T. mucoides.…”
Section: Discussionmentioning
confidence: 84%